Inne lustra. Pseudonarcystyczne reprezentacje w utworach Haliny Poświatowskiej i Wisławy Szymborskiej - Zalewski, Cezary (Przestrzenie Teorii, 2009)
The article analyses and compares two poetical texts written by women. The texts use a motif of a mirror in both literal and metaphorical way. The author compares H. Poświatowska’s and W. Szymborska’s poems to question traditional twentieth-century reception of Narcissus’ motive. The proposal that arises is to see this motive as an illusion. Any woman that watches herself in a mirror does not seek just for her sight, but also for a sight of “an other” – a man. Quoting these gives, in the author’s opinion, an argument to say that a woman watching her reflection is not able to converge the mythical Narcissus’ archer. Appearance of a man that was sought mediates the act of self-contemplation in which one that was watching gets an access to herself by both body and mind aspect. The access is possible only under a condition of “sight of an other” mediacy. The subject in women’s lyrics is liable and dependent on what can be seen as a typical feature of its modern version. This liability and dependency is being carefully masked in lyrics written by men that explore the myth of Narcissus.